Symboliczne aspekty wykorzystania ognia w późno średniowiecznej i wczesnonowożytnej przestrzeni rodziny polskiej - Justyna Rogińska (In Gremium. Studies in History, Culture and Politics, 2015)
Symbolic aspects of using a fire in late medieval and early modern polish family spaceThe article is an attempt to reconstruct a symbolic significance of the fire in life of polish family between XIII and XVIII centuries. On the basis of analyze of rich ceremonialism, which can be found in home, household and church space, some types of this element were defined by way of example. The basicmerit of a fire is its consumer value, which providing family with life was the base of assessment and creating of additional sense. In symbolic stratum the main role played a ritual fire, which being a part of receiving ritual admitted new members of community (for example, children, women). There wasa fire in magical acts and fortune-telling in everyday practice. Made cyclically or by accident purifying fire protected house and cattle from contagion, dark forces and animal pests. Fire is also a destructive power, of which man was afraid and from which protected his family. The value of flame was also anarea of death. Ritual gestures and acts usually used element’s substitutes like candle, smoke, ashes and stove. The rich symbolism of fire, its multi-aspect using and great variety of forms are an evidence of importance of this element in a family’s community space.